(untitled) (Bangladesh Journal of Botany, 2008)
Mite infestation is one of the main factors restricting jute production in Bangladesh. The utilization of jute cultivars tolerant to mite attack can be one of the most economic strategies for expanding jute production. Among jute genotypes, C. olitorius O-7/95 has been reported to be most tolerant to mite attack. SSR or microsatellite markers for jute have been successfully used in distinguishing mite sensitive and tolerant jute varieties. To increase selection efficiency for mite tolerance we have used an F2 population of O-7/95 and O-72 (sensitive to mite attack) to map a number of these microsatellite markers and to determine their linkage with mite tolerant trait. A preliminary genetic linkage map based on 35 F2 populations, was constructed using software MAPMAKER/EXP (ver 3.0b). This map was based on ten SSR markers and a phenotypic marker (M-11) related to mite sensitivity. In this analysis mite resistance has been found to be linked with a SSR marker, M-66 at LOD threshold of 3. This marker has the potential of being useful in Marker Assisted Selection (MAS) in jute breeding programs for selection of lines resistant to mite. Key words: Jute, Mite tolerance, SSR marker, Linkage mapping doi:10.3329/bjb.v37i2.1725 Bangladesh J. Bot. 37(2): 161-171, 2008 (December)